Analisis Kecerdasan Emosional dan Penyesuaian Diri Siswa SMK X di Bekasi: Tugimin Supriyadi, Fitri Febriani - Fitri Febriani; Tugimin Supriyadi (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
The purpose of this study was to determine the relationship between emotional intelligence and self-adjustment in class X SMK Mandalahayu 1 Bekasi. The sampling technique used in this study was probability sampling with 137 respondents who were students from SMK Mandalaayu 1 Bekasi. The measuring instrument used is the emotional intelligence scale and the self-adjustment scale. The results of this study indicate that the coefficient value between emotional intelligence variables and self- adjustment variables is 0.620 with a significance level (p) of 0.000 (p>0.05), so it is stated that there is a relationship between emotional intelligence variables and self- adjustment variables for SMK Mandalahayu 1 Bekasi students.